Perancangan, Implementasi Monitoring dan Kontrol Alat Pemanggang Kopi - Tampubolon, Friyogi; Pratama, Yohanssen; Dirgayussa, I Gde Eka (ELKHA : Jurnal Teknik Elektro, 2020)
Coffee roasting is the process of removing the water that is exist in the coffee beans. Roasted coffee beans will change weight and give a nice aroma and taste. The longer the coffee beans are roasted, the color of the coffee beans will continue getting darker blackish brown. The roasting level of coffee beans is determined from the change in color of coffee beans starting from light, medium and dark. Roasting coffee beans that develop on a home industry scale is still manual, that is, using more human labor in its operation. Therefore, this research will be made an automatic coffee roasting machine using a heater to heating the coffee beans, a DC motor to stir roasted coffee beans and a webcam to monitor changes in the color of coffee beans when roasted. Components of heating elements and motors controlled by Arduino Mega 2560 microcontroller while the webcam is connected with Raspberry Pi 3. As a component of performance that has been met with sensors as data collectors, microcontrollers as data processors and actuators as control systems. In this researh 3D modeling for a roasting container is done using SketchUp 3D design software. The results of the coffee roasting machine can meet the requirements of the system designed in accordance with the roasting level desired by the user and the thermocoupel give a better result in reading the temperature parameter compared to infrared thermometer. In 4,5 minutes the difference reading in temperature reach 27,50C between two sensors.